A Novel Gene Signature Associated With “E2F Target” Pathway for Predicting the Prognosis of Prostate Cancer - Xia, Haoran; Wang, Miaomiao; Su, Xiaonan; Lv, Zhengtong; Yan, Qiuxia; Guo, Xiaoxiao; Liu, Ming (Frontiers in Molecular Biosciences, 2022)
Background: The effect of “E2F Target”-pathway on prostate cancer is not clear. It is necessary to establish a “E2F Target”- related gene signature to predict prognosis and guide the future research. Methods: The “E2F Target”-related gene signature was established by univariate and LASSO cox regression analysis, and its predictive ability was verified in multiple cohorts. More importantly, the enrichment pathway, immune microenvironment and drug sensitivity of activated “E2F Target” pathway have also been explored. Results: The “E2F Target”-related gene signature consisted of MXD, PLK1, EPHA10 and KIF4A. Patients with high risk scores showed poor prognosis, therapeutic resistance and immunosuppression, as also as abnormal growth characteristics of cells. Tinib-drugs showed high sensitivity to the expression of MXD3 and EPHA10 genes. Conclusions: The research established a “E2F Target”-related signature for predicting prognosis of prostate cancer, which is helpful to formulate individualized detection and treatment, and provide a theoretical basis for future research.